RANCANG BANGUN VACUM PADA SUCTION PUMP BERBASIS MIKROKONTROLLER - Gultom, Willy Gusllah; Situmorang, Harold; Ulina, Sri; Abdillah, Khairil (Prodi Teknik Elektromedik Universitas Sari Mutiara Indonesia, 2022)
Suction Pump is a medical device that functions to suck fluids that are not needed by the body during the operation process, such as blood, stomach contents, and so on. Then the sucked liquid is accommodated in a container. Suction mostly still uses a manometer to read the results of the pressure sucked by the motor so that the user has difficulty reading it, the author makes modifications to the suction pump which is equipped with a pressure sensor. This sensor will change the results of the suction pressure on the vacuum motor into digital which will be displayed on the LCD. This research will be conducted at the Sari Mutiara University lab. The type of research method is experimental research, namely conducting direct experiments on tools designed to build. The measurement results of the suction pressure will be displayed on the LCD, with measurements according to the standard of the suction pump suction in general.